Students' high order thinking skill in solving mathematical problems in terms of intrapersonal intelligence - Budiyanta, Elix; Fitriyani, Harina (International Journal on Teaching and Learning Mathematics, 2023)
High order thinking skills (HOTS) is a person's thought process by memorizing and remembering, but it involves critical thinking, argumentation, and making decisions. The purpose of this study was to find out the profile of the student's HOTS in solving mathematical problems in terms of students' intrapersonal intelligence on rectangular material. This type of research is qualitative descriptive. The subjects consisted of six students from one of the state senior high schools in Yogyakarta, each of 2 students with high, medium, and low intrapersonal intelligence. Data collection techniques using questionnaires, written tests, and interviews. The instrument of this study consisted of an intrapersonal intelligence questionnaire, HOTS-based test questions, and interview guidelines. Data were analyzed consist of reducing, interpretation, and concluding. The results showed that the subject of high intrapersonal intelligence in solving mathematical problems could meet the indicators of HOTS ability, namely the ability to analyze in the sorting category of cognitive processes, organizing, and attributing and the ability to evaluate in checking categories. In contrast, the subject of medium and low intrapersonal intelligence can only meet the indicator of ability to analyze in the sorting categories of the cognitive process.